KOMPOSISI JENIS DAN JUMLAH BURUNG LIAR YANG DIPERDAGANGKAN DIJAWA BARAT - Tri Haryoko (BERITA BIOLOGI, 2010)
Wildbird trade is a threat to the conservation of birds population in Indonesia. The main causes of wildbirds extinction are habitat loss or habitat destruction and poaching for trade.The aim of this study was to identify trade of wildbird species in West Java. The survey was carried out in October to November 2008.A total of 2080 birds (consisted of 67 species and 29 family) were traded in Bandung, Garut and Tasikmalaya areas.Bird markets in those three areas traded 1051, 496 and 533 birds respectively. The result of one way analysis of variance (anova) using SPSS 13.0 F , ll15)= 2,398 < Ftabel = 3,042, showed no significant different in the above mentioned three bird markets.